2014
DOI: 10.1021/la5021884
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Guiding of Kinesin/Microtubule-Based Microtransporters in Microfabricated Tracks

Abstract: Microtransporters using cargo-laden microtubules propelled by kinesin motors are attractive for numerous applications in nanotechnology. To improve the efficiency of transport, the movement of microtubules must be guided by microfabricated tracks. However, the mechanisms of the guiding methods used are not fully understood. Here, using computer simulation, we systematically studied the guiding of such microtransporters by three different types of guiding methods: a chemical boundary, a physical barrier, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 64 publications
1
10
0
Order By: Relevance
“…Chemical Guiding by the Kinesin Trail: The Case for Pheromonic Interactions. Prior work on filament guiding on motor protein-coated surfaces has shown that filaments follow permanent trails of motors created by chemical surface patterning if the required change in the angle of motion is small (<15°for microtubules), 75,77,78 or if the microtubule is already aligned with a narrow track and the radius of curvature is large enough (>17 μm). 79 Trails of motors have also been printed by deposition of motor-covered microtubules.…”
Section: Resultsmentioning
confidence: 99%
“…Chemical Guiding by the Kinesin Trail: The Case for Pheromonic Interactions. Prior work on filament guiding on motor protein-coated surfaces has shown that filaments follow permanent trails of motors created by chemical surface patterning if the required change in the angle of motion is small (<15°for microtubules), 75,77,78 or if the microtubule is already aligned with a narrow track and the radius of curvature is large enough (>17 μm). 79 Trails of motors have also been printed by deposition of motor-covered microtubules.…”
Section: Resultsmentioning
confidence: 99%
“…To test the hypothesis that the active probes are oriented to the direction which minimized their accumulated bending energy, we performed a simulation study. We adopted and modified a computer simulation of an in vitro gliding assay of microtubules for this study (see ‘Methods' and Supplementary Figs 11 and 12 ) 28 . We simulated the alignment of the active probes induced by the substrate compression.…”
Section: Resultsmentioning
confidence: 99%
“…The simulation method was adopted from a previous work 28 , and modified for this study. Briefly, we simulated the three-dimensional movement of microtubules propelled by kinesin motors on compression of the substrate.…”
Section: Methodsmentioning
confidence: 99%
“…The simulation method was based on our previous work [7], and extended to include applied force to microtubules. In the following, we briefly summarize the simulation method.…”
Section: Simulation Methodsmentioning
confidence: 99%
“…In order to simulate the sidewise slipping and detachments, microtubules and kinesins have to be explicitly modeled. We have recently developed a simulation which explicitly models cytoskeletal filaments and motor proteins [7] [8]. In this study, we extended the simulation to include applied forces, and investigated whether the extended simulation reproduced experimental results.…”
Section: Introductionmentioning
confidence: 99%